Towards Territorial Sustainability Systems: A step forward - Jose M. Barrutia; Carmen Echebarria; Patrick Hartmann; Vanessa Apaolaza; Ainhize Eletxigerra; Alexander Velez (European Regional Science Association (ERSA), 2015)
Regional research has focused on the innovation-competitiveness-growth chain, which is implicit in Territorial Innovation Systems. This literature has neglected or subordinated social and ecological regional conditions. We see this study as a first step towards more systematic research on what might be termed ?Territorial Sustainability Systems.? We study local sustainability planning processes under the label of Local Agenda 21 (LA21) in Italy. A model is proposed in which the integration of resources explains the engagement of municipal authorities with LA21-type processes that are implemented within a networking structure. Two types of resources, municipal (or internal resources), and relational resources, are considered. Relational resources stem from: (1) dyadic relations with higher levels of government (HLG), and (2) network relations (municipality-HLG-municipality). The model is tested by considering the perceptions of local authorities who are in charge of LA21 processes in Italy. The results show moderate/low engagement with LA21 processes, which is explained by moderate/poor levels of relational resources. Our findings indicate that local authority engagement with LA21-type processes requires a systemic perspective, where HLG and municipalities integrate and combine their resources and create new purposefully-led resources through regular and intense interactions.
Keywords: Q56; Q57; Q58; 330; Local Agenda 21; Italy; private resources; relational resources; municipalities